1990
DOI: 10.1002/prep.19900150403
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Reaction of SrCO3 on the burning rate of ammonium perchlorate propellants

Abstract: The buring rate of ammonium perchlorate (AP) composite propellants is decreased significantly by the addition of SrCO3 without increasing the pressure exponent of burning rate. Results of microthermocouple measurements indicate that the burning surface temperature is increased from 700 K to 970 K by the addition of SrCO3, although the heat release rate in the gas phase is remained unchanged. DTA (differential thermal analysis) and TG (thermogravimetry) experiments were also carried out in order to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A combination of calcium citrate and strontium carbonate had lowest burning rate than alone, which is the same with the combination of ammonium oxalate and SrCO 3 [22]. The mechanism of SrCO 3 as BRS was investigated by thermal analysis of AP and AP/SrCO 3 [40]. The result indicated that the decomposition process of AP was substantially altered by the addition of SrCO 3 , which was caused by the lowered activation energy of AP decomposition.…”
Section: Burning Rate Suppressants For Ap‐based Composite Propellantsmentioning
confidence: 70%
“…A combination of calcium citrate and strontium carbonate had lowest burning rate than alone, which is the same with the combination of ammonium oxalate and SrCO 3 [22]. The mechanism of SrCO 3 as BRS was investigated by thermal analysis of AP and AP/SrCO 3 [40]. The result indicated that the decomposition process of AP was substantially altered by the addition of SrCO 3 , which was caused by the lowered activation energy of AP decomposition.…”
Section: Burning Rate Suppressants For Ap‐based Composite Propellantsmentioning
confidence: 70%
“…11 Similar concern has also been expressed by Guirao and Williams. 19 Therefore, the failure to give observable changes in surface temperature with pressure by some experimental studies [13][14][15] may be attributed to the dimensional inadequacy of temperature detectors in the very high-thermal-gradient environment. For the present investigation, taking the thermocouple junction to be a sphere of diameter equal to two times the wire diameter, viz., 15 m, and noting that the maximum burning rate at 1 bar is around 1 mm /s the time to reach 99% of the environmental temperature can be in the range of 1.5 -4.5 ms. [20][21][22] Furthermore, in a supporting manner, the time that the burning surface requires to cross the thermocouple junction is much longer, around 15 ms, and the condensed-phase temperature gradient at 1 bar is about 1 K/ m. Hence, the temperature measurement at 1 bar is expected to be accurate and the conditions for accuracy only improve at further lower pressures.…”
Section: Methodsmentioning
confidence: 93%
“…The experimental methods, adopted to determine this temperature, include 1) the technique using infrared emission from the burning surface, [8][9][10][11] 2) the backcalculation from the thickness over which the AP crystal lattice changes from orthorhombic into cubic, 12 and 3) the ne-thermocouple technique. [13][14][15][16][17] Powling and Smith, [8][9][10] using the infrared emission technique, measured from subatmospheric pressures ( 0.033 bar) to higher atmospheric pressures ( 20.40 bar) the surface temperatures of 1) fuel-lean as well as fuel-rich mixtures of AP and some readily gasi ed fuels such as paraformaldehyde (from subatmospheric to above-atmospheric pressure ranges), [8][9][10] 2) a fuel rich mixture of AP/polystyrene and fuel-rich propellants of AP/polyisobutene (subatmospheric to atmospheric pressure ranges), 8,10 and 3) fuel-rich propellants of AP/polyurethane (PU) (at atmospheric pressure only). 8 The burning rates of these compositions were widely varied more than vefold by the changes in pressure, AP particle size, and fuel/ oxidizer ratio, and also by the addition of some catalysts such as copper chromate.…”
Section: Introductionmentioning
confidence: 99%
“…The burning rate remains unchanged on adding this catalyst in the low-pressure region at about 0.3 MPa. The pressure exponent of the burning rate is decreased from 0.70 to 0.50 at 343 K, and from 0.70 to 0.55 at 243 K. The temperature sensitivity of the burning rate is also decreased from 2.61 × 10 −3 to 1.33 × 10 −3 K −1 at 1.0 MPa when 2.0% SrCO 3 is added [16,17].…”
Section: Srco 3 Negative Catalystmentioning
confidence: 99%